Hormone signalling pathways are differentially involved in quantitative resistance of potato to Phytophthora infestans. (26th June 2015) - Saubeau, G.; Perrin, F.; Marnet, N.; Andrivon, D.; Val, F.
Abstract : Quantitative resistance may depend on the effectiveness of PAMP‐triggered immunity. This study highlights the diversity of mechanisms involved in the quantitative resistance of potato to Phytophthora infestans . The investigation focused on the implication of the hormone signalling pathways induced in four potato genotypes by a concentrated culture filtrate (CCF) of P. infestans . The genotypes were ranked according to their level of resistance to P. infestans and discriminant analysis of gene expression profiles separated the most resistant genotype from the three others, particularly because of a strong induction of the salicylic acid (SA) pathway. In this genotype, transcripts involved in the SA pathway, EDS1, WRKY1, PR‐1 and PR‐2, were induced by CCF. SA pathway involvement was confirmed by a peak of SA accumulation 12 h after elicitation and by the induction of jaz1 ( jasmonate Zim domain protein 1 ) transcripts, which inhibit defence responses mediated by jasmonic acid (JA). By contrast, neither a significant induction of SA‐mediated responses nor an accumulation of free SA and PR‐2 were observed in the other resistant or two susceptible cultivars. Expression of genes in the ET and JA pathways was either not, or weakly, induced by CCF in potato. Finally, the involvement of signalling pathways was genotype dependent rather than correlating with resistance level.